New hope for tsetse control - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
A new method for controlling the tsetse fly is currently being tested. The tsetse fly is responsible for transmitting the potentially fatal disease sleeping-sickness in humans, and the similar disease, nagana, in cattle. The new method uses the...